(untitled) (Boston, 2004)
Beginning and Intermediate Algebra extends the successful Streeter/Hutchison/Bergman series of developmental mathematics worktexts to another course. The book combines topics from the successful Beginning Algebra worktext and topics from the Intermediate Algebra worktext. The book utilizes Streeter's popular pedagogy, including active learning backed by Check Yourself exercises, in this combined algebra book. The worktext is accompanied by numerous useful supplements, including a SMART CD-ROM, videos, and Online Learning Center.
Keywords: Đại số,Algebra